2015
DOI: 10.5603/ait.2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

Ogłuszone serce neurogenne — czy uwzględniamy to rozpoznanie u chorych z ostrym uszkodzeniem ośrodkowego układu nerwowego i niewydolnością serca?

Abstract: Neurogenic stunned myocardium (NSM) is defined as myocardial injury and dysfunction of a sudden onset, occurring after various types of acute brain injury as a result of an imbalance in the autonomic nervous system. The typical spectrum of clinically observed abnormalities includes acute left ventricular failure, not uncommonly progressing to cardiogenic shock with hypotension that requires inotropic agents, pulmonary oedema and various arrhythmias. Commonly-seen electrocardiographic changes include: prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 39 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Until recently, neurogenic stunned myocardium (NSM) was defined as the myocardial injury and dysfunction of a sudden onset, occurring after acute brain disease as a result of autonomic disturbances, which may be responsible for the cardiac injury after stroke[6,7]. The clinical features observed include arrhythmia, myocardial necrosis, ECG changes, pulmonary edema, and acute left HF which is not uncommon to progress to cardiogenic shock[8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Until recently, neurogenic stunned myocardium (NSM) was defined as the myocardial injury and dysfunction of a sudden onset, occurring after acute brain disease as a result of autonomic disturbances, which may be responsible for the cardiac injury after stroke[6,7]. The clinical features observed include arrhythmia, myocardial necrosis, ECG changes, pulmonary edema, and acute left HF which is not uncommon to progress to cardiogenic shock[8].…”
Section: Discussionmentioning
confidence: 99%
“…Oppenheimer et al[9] induced ECG changes in rats similar to those found after ischemic stroke, supporting the notion of neurogenic cardiac injury. NSM, which can develop in any acute CNS pathology, has a poorly understood pathology[8]. Most models for the etiopathology of NSM involve a subarachnoid hemorrhage (SAH)[10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCS was diagnosed according to the following criteria [ 10 ]: (1) no previous history of heart disease; (2) clear diagnosis of acute ischemic stroke; (3) any secondary cardiac damage manifestations. The manifestation includes: (1) ECG changes, including ST segment elevation or depression, T wave changes and QT prolongation [ 11 13 ]; (2) cardiac dysfunctions in echocardiography such as left ventricular diastolic dysfunction, [ 14 ] abnormal ventricular wall motion, [ 15 ] and decreased left ventricular ejection fraction [ 16 ]; (3) elevated peripheral cardiac markers by laboratory tests including troponin [ 17 ] and B-type natriuretic peptide [ 18 ].…”
Section: Methodsmentioning
confidence: 99%